2014
DOI: 10.1002/pbc.25383
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal differences in aerobic capacity between children with sickle cell anemia and matched controls

Abstract: Background The purpose of this study was to compare longitudinal trajectories of maximal aerobic capacity in children with sickle cell anemia (SCA) and matched healthy controls, and explore whether these trajectories were associated with selected physiologic variables. Procedures Children with SCA (n=33) and healthy controls (n=30) matched at baseline for race, sex, Tanner stage, height, and weight completed three consecutive annual fitness assessments (VO2peak). Data were compared between the groups at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The physical fitness of these AYAs were fair to poor as indicated by the range of VO 2 peak values. The mean VO 2 peak of 19.2 mL/kg/min is similar to findings in other studies of AYAs with SCD, where mean VO 2 peaks have ranged from 23 to 28 (Liem et al, 2009;Liem et al, 2015;Watson et al, 2015), and notably lower than healthy AYAs, where VO 2 peaks have been ranged from 28 to 52 (Eisenmann, Laurson, & Welk, 2011;Liem et al, 2015;Robbins, Pender, Ronis, Kazanis, & Pis, 2004;Schneider, Dunn, & Cooper, 2009;Watson et al, 2015;Zamunér et al, 2011). Studies of sedentary individuals within this age category have reported VO 2 peaks ranging from 24 to 33 ml/kg/min (Welch et al, 2007;Zamunér et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The physical fitness of these AYAs were fair to poor as indicated by the range of VO 2 peak values. The mean VO 2 peak of 19.2 mL/kg/min is similar to findings in other studies of AYAs with SCD, where mean VO 2 peaks have ranged from 23 to 28 (Liem et al, 2009;Liem et al, 2015;Watson et al, 2015), and notably lower than healthy AYAs, where VO 2 peaks have been ranged from 28 to 52 (Eisenmann, Laurson, & Welk, 2011;Liem et al, 2015;Robbins, Pender, Ronis, Kazanis, & Pis, 2004;Schneider, Dunn, & Cooper, 2009;Watson et al, 2015;Zamunér et al, 2011). Studies of sedentary individuals within this age category have reported VO 2 peaks ranging from 24 to 33 ml/kg/min (Welch et al, 2007;Zamunér et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Exercise capacity, defined by oxygen uptake at peak exercise (peak VO 2 ) during cardiopulmonary exercise test (CPET), is a determinant of mortality and a treatment target in patients with DD in other clinical settings . Peak VO 2 is decreased in a significant proportion of children and young adults with SCA compared to normal controls even after controlling for anemia . The ventilation‐to‐carbon dioxide production slope at maximum exercise (VE/VCO 2 slope) is another important exercise measure that assesses ventilation efficiency and has been shown to correlate with left ventricular filling pressures and mortality in patients with DD .…”
Section: Introductionmentioning
confidence: 99%
“…1 and young adults with SCA compared to normal controls even after controlling for anemia. [10][11][12] The ventilation-to-carbon dioxide production slope at maximum exercise (VE/VCO 2 slope) is another important exercise measure that assesses ventilation efficiency and has been shown to correlate with left ventricular filling pressures and mortality in patients with DD. 9,10,13,14 The VE/VCO 2 slope has also been reported to be abnormal in patients with SCA.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of SCA is characterized by accelerated red blood cell breakdown, microvascular occlusion, and a pro-inflammatory state—all of which may lead to acute pain episodes as well as acute and chronic organ injury over the lifespan. Although triggers for acute pain episodes vary but may include high intensity exercise, the safety of maximal exercise testing in children with SCA has now been demonstrated [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%